The effects of Copenhagen football test on glutathione reductase and catalase activity in female football players - Abedi, B.; Fatolahi, H.; Kouhidehkordi, S.; Abbass Zolfaghari, G. (Asian Journal of Sports Medicine, 2017)
Background: Changes in oxidative stress in response to vigorous exercise is of prime importance. In this area, the changes of catalase activity and glutathione reductase are very important. However, the results of the activity of antioxidants, particularly in erythrocytes, are not unified. Football is a heavy exercise. Therefore, the present study aimed at analyzing the effects of Copenhagen football test on the glutathione reductase and catalase activity.